Of mice and men. - Shemilt, Peter (Bookseller, 2003)
The article provides suggestions for booksellers to increase their sales of computer books. Earlier, it did not seem to matter how much knowledge the bookseller or sales representative had about the information technology industry, where the section was located instore or how it was organised. In 2002 the computer book sector in Great Britain has changed completely, affected by a global technology recession that has seen millions of pounds lost at the stock market value of leading technology companies and thousands of employees lose their jobs. Despite the economic recession, fundamentally there is a very strong book market that demands quality, value and availability. "Computing is one of those sections which follows trends, like music or fashion, but much more so," explains Mike Woods of Waterstone's Online. "One of the problems for booksellers is that the range of books is huge and many of the titles are very technical, so it can be confusing." Martin Cox, senior bookseller at Blackwell's Broad Street, Oxford, agrees: "Computer bookselling can be very different from selling other types of books." The article suggests the booksellers to include books on Macromedia's MX suite of products in their computing section. The MX range includes: Flash MX for creating rich content, graphics and applications; Dreamweaver MX for building and managing websites andapplications in a single environment; and Coldfusion MX to integrate applications with databases, XML and web services.